Integral cluster set-up for complex compound composites syntesis - Yakovin, S.D.; Dudin, S.V.; Zykov, A.V.; Farenik, V.I. (Вопросы атомной науки и техники, 2011)
At present study the result of development and investigations of cluster technological set-up for synthesis of
complex compound composites is demonstrated. The present set-up consist of complimentary DC-magnetron system,
RF-inductive plasma source and ion source. The system allows to independently form the fluxes of metal atoms,
chemically active particles, ions and also to synthesize the thin films of complex compound composites, including
nanocomposites. Various types of high-quality coatings such as Al2O3, AlN, TiO2, TiN, ZrO2 and others with thickness
up to 10 mkm have been synthesized using the described set-up. Представлено результати розробки і дослідження технологічної установки для синтезу складно-
композитних сполук на поверхні. Установка складається з комплементарних модулів магнетрона постійного
струму, ВЧ-індукційного джерела плазми і джерела іонів. Система дозволяє незалежно формувати потоки
металевих атомів, хімічно активних часток, іонів і синтезувати тонкі складнокомпозитні плівки, включаючи
нанокомпозити. На цій установці було отримано різні типи високоякісних покриттів, таких як Al2O3, AlN, TiO2,
TiN, ZrO2 та ін., товщиною до 10 мкм. Представлены результаты разработки и исследования технологической установки для синтеза сложно-
композитных соединений на поверхности. Установка состоит из комплементарных модулей магнетрона
постоянного тока, ВЧ-индукционного источника плазмы и источника ионов. Система позволяет независимо
формировать потоки металлических атомов, химически активных частиц, ионов и синтезировать тонкие
сложнокомпозитные пленки, включая нанокомпозиты. На представленной установке были получены различные
типы высококачественных покрытий, таких как Al2O3, AlN, TiO2, TiN, ZrO2 и др., толщиной до 10 мкм.